Digital Literacy-Based Sole Learning Model for Improving Student Learning Outcomes and Activeness - Wedasuwari, Ida Ayu Made; Sari, Ni Wayan Eminda; Erawan, Dewa Gede Bambang (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2025)
Students often experience difficulties in achieving optimal learning outcomes and showing consistent engagement in learning. The low involvement of students in the teaching and learning process is a serious challenge in improving the quality of education in the digital era. This study aims to analyze the effectiveness of the digital literacy-based Self-Organized Learning Environment (SOLE) learning model in improving learning outcomes and optimizing student activeness. This research is a quantitative study with a one-group pretest-posttest design. The subjects of this study were students, who were taking syntax course. Data collection techniques used learning outcomes tests and student activeness observations, with instruments in the form of pretest-posttest questions and activity observation sheets. Data analysis was carried out by Kolmogorov-Smirnov and Shapiro-Wilk normality tests, as well as paired sample t tests to determine significant differences between pretest and posttest. The results showed a significant increase in learning outcomes and student activeness as evidenced by an increase in the average pretest score after treatment. The conclusion of this study is that the application of the digital literacy-based SOLE model is effective in improving student learning outcomes and activeness. The implication of this study shows that the use of technology-based learning approaches that provide learning independence can be a strategic alternative to improve the quality of education in the digital era.